2009
DOI: 10.1007/s11581-008-0312-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of ionic conductivity in the composite solid electrolyte system: TlI–Al2O3

Abstract: This paper reports the heterogeneously doped alumina (Al 2 O 3 ) on the ionic conductivity of thallium iodide. Composite materials of formula (1−x) TlI-xAl 2 O 3 , x = 0-0.7 have been prepared and studied by X-ray diffraction, differential scanning calorimetry, and electrical conductivity. X-ray diffraction and differential scanning calorimetry proved the formation of composite in this binary system. The maximum enhancement observed is about three orders of magnitude with respect to the host material. The enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…The activation energy values show an opposite trend i.e. as the electrical conductivity increases, the activation energy decreases [26,27]. Hence, CuFe 2 O 4 has the maximum activation energy (3.220 eV) while PANI has the lowest (1.761 eV).…”
Section: Electrical Properties Of the Synthesized Materials (Electricmentioning
confidence: 99%
“…The activation energy values show an opposite trend i.e. as the electrical conductivity increases, the activation energy decreases [26,27]. Hence, CuFe 2 O 4 has the maximum activation energy (3.220 eV) while PANI has the lowest (1.761 eV).…”
Section: Electrical Properties Of the Synthesized Materials (Electricmentioning
confidence: 99%
“…However, the one at higher frequency results from bulk resistance while that at low frequency resulted from grain boundary resistance contribution. It has been found that the idealized impedance plot of such material consists of a semicircle attributed to grain and grain boundary as well as low frequency inclined spike due to the ionic polarization and electrochemical reactions, occurring at the electrode interface [14,24]. The appearance of the spikes is an indication that the conduction in these materials is ionic in nature [16].…”
Section: Impedance Measurementsmentioning
confidence: 99%
“…where the resistance of grain (R g ) can directly be obtained from the intercept of the Z -axis [14]. The angular frequency of grain (ω g ) is obtained at the maxima of the semicircles.…”
Section: Impedance Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…LiI, AgI, AgCl, CdI 2 , TlI, CsHSO 4 , CsH 2 PO 4 and oxide insulators like SiO 2 , Al 2 O 3 , ZrO 2 , Fe 2 O 3 , MgO, TiO 2 etc. [7][8][9][10][11][12][13][14][15][16][17][18][19]. This method is recognized as an easier and more efficient because of not only the enhanced room temperature ionic conductivity, but also it boosts up the thermal and mechanical stability of the material.…”
Section: Introductionmentioning
confidence: 99%